The State of Ambient Air Quality in Two Ugandan Cities: A Pilot Cross-Sectional Spatial Assessment - Kirenga, Bruce J.; Meng, Qingyu; Gemert, Frederik van; Aanyu-Tukamuhebwa, Hellen; Chavannes, Niels; Katamba, Achilles; Obai, Gerald; Molen, Thys van der; Schwander, Stephan; Mohsenin, Vahid (International journal of environmental research and public health, 2015)
Air pollution is one of the leading global public health risks but its magnitude in many developing countries’ cities is not known. We aimed to measure the concentration of particulate matter with aerodynamic diameter <2.5 μm (PM2.5), nitrogen dioxide (NO2), sulfur dioxide (SO2), and ozone (O3) pollutants in two Ugandan cities (Kampala and Jinja). PM2.5, O3, temperature and humidity were measured with real-time monitors, while NO2 and SO2 were measured with diffusion tubes. We found that the mean concentrations of the air pollutants PM2.5, NO2, SO2 and O3 were 132.1 μg/m3, 24.9 μg/m3, 3.7 μg/m3 and 11.4 μg/m3, respectively. The mean PM2.5 concentration is 5.3 times the World Health Organization (WHO) cut-off limits while the NO2, SO2 and O3 concentrations are below WHO cut-off limits. PM2.5 levels were higher in Kampala than in Jinja (138.6 μg/m3 vs. 99.3 μg/m3) and at industrial than residential sites (152.6 μg/m3 vs. 120.5 μg/m3) but residential sites with unpaved roads also had high PM2.5 concentrations (152.6 μg/m3). In conclusion, air pollutant concentrations in Kampala and Jinja in Uganda are dangerously high. Long-term studies are needed to characterize air pollution levels during all seasons, to assess related public health impacts, and explore mitigation approaches.
Keywords: Ambient air pollution; Particulate matter; Nitrogen dioxide; Sulfur dioxide; Ozone